Prenatally diagnosed pulmonary atresia with ventricular septal defect: echocardiography, genetics, associated anomalies and outcome. Issue 10 (17th March 2006) - Vesel, S; Rollings, S; Jones, A; Callaghan, N; Simpson, J; Sharland, G K
Abstract : Objective: To assess the accuracy of prenatal diagnosis, the association with genetic and extracardiac anomalies, and outcome in fetuses with isolated pulmonary atresia with ventricular septal defect (PA-VSD). Design and setting: Retrospective study in a tertiary centre for fetal cardiology. Patients and outcome measures: Echocardiographic video recordings of 27 consecutive fetuses with PA-VSD were reviewed for: (1) intracardiac anatomy; (2) presence of confluence and size of the branch pulmonary arteries; (3) source of pulmonary blood supply; and (4) side of the aortic arch. Postmortem and postnatal data were added. Karyotyping was performed in 25 patients and, in 23 of these, fluorescent in situ hybridisation to identify 22q11.2 deletion. Results: PA-VSD was correctly diagnosed in 19 of 21 patients (90%) with postnatal or autopsy confirmation of diagnosis. Central pulmonary arteries were correctly identified in 79% (15/19), the source of pulmonary blood supply in 62% (13/21) and major aortopulmonary collateral arteries in 44% (4/9). Aneuploidy was detected in 4 of 25 patients (16%) and 22q11.2 deletion in 6 of 23 patients (26%). Five of 27 patients (19%) had extracardiac anomalies. Eleven pregnancies were interrupted. Eleven of 16 liveborn babies survived. Neonatal survival was 15 of 16 (94%, 95% confidence interval (CI) 70 to 100), one-year survival was 9 of 12 (75%, 95% CI 43 to 95) and two-year survival was 5 of 9 (56%, 95% CI 21 to 86). Conclusion: PA-VSD can be diagnosed by fetal echocardiography with a high degree of accuracy. However, it can be difficult to determine the morphology of the central pulmonary arteries and to locate the source of pulmonary blood supply. In most liveborn infants, complete surgical repair can be achieved.